The Effectiveness of Digital Pop-Up Book Media on Descriptive Writing Skills in Elementary School Students - Putri, Charysma Laylatul; Nuroh, Ermawati Zulikhatin (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
This research aims to encourage the development of students through the application of digital-based learning media, considering that most educators still pay little attention to the use of media as learning tools in the digital era. The focus of this study is to investigate the improvement of students' descriptive writing skills through the use of digital pop-up book media. The method used in this study is a quantitative method with a one-group pretest-posttest design. The research population consisted of fifth-grade elementary school students, with a sample of 26 students from Class V A. The researcher used a writing skills assessment rubric that included aspects of content, organization, grammar, style, spelling, and punctuation. The data collection technique employed pretest and posttest questions, and the data analysis utilized a paired t-test. The results showed a positive influence of using digital pop-up book media on the descriptive writing skills of elementary school students. This was proven by the t-test results, which showed a sig. value. (2-tailed) of 0.000 < 0.05 means that Ho is rejected and Ha is accepted. In other words, the use of digital pop-up book media has a significant effect on the descriptive writing skills of grade V A students at SDN Sumorame. Therefore, digital pop-up book media can be an innovative tool in elementary school learning and has the potential to be further developed according to students' needs.